SUBACUTE SCLEROSING PANENCEPHALITIS – CHANGES IN PHENOTYPE DURING THE LAST DECADE : SUBACUTE SCLEROSING PANENCEPHALITIS - Kravljanac, Ružica; Palić, Ilija; Vučetic Tadić, Biljana (Medical Research, 2023)
Introduction: Subacute sclerosing panencephalitis (SSPE) is a rare, progressive, neurodegenerative disease with poor outcome. Anti-measles vaccination contributed to decreasing number of SSPE patients, but not to eradication. The aim of our study is to evaluate the course of disease in our SSPE patients with focus on vaccinated children. The main goal is considering the possibilities for improving the prevention of disease.Methods: A retrospective study included the patients with SSPE treated in period from December 2010 until December 2020 in Pediatric Clinic in Institute. The inclusion criteria is the patients with diagnosis of SSPE based on clinical presentation, neuroimaging, electroencephalography and positive IgG anti-measles antibodies, both in serum and CSF. Results: Five children with fulminant course of SSPE were included. All patients were suffering measles at the infancy. Three of them were vaccinated against measles, while two were not vaccinated. All of them are previously healthy, immune-competent children, with normal global development. The course was extremely fulminant with lethal outcome within three months from initial symptoms in four cases. Progressive motor and cognitive decline, behavior changes, movement disorders, myoclonic jerks and seizures were dominated in clinical presentation.Conclusion: Despite vaccination era, SSPE hasn’t been vanished. The increasing number of vaccinated immune-competent children with fulminant form of SSPE and history of measles infection during the infancy were treated in our Clinic. As a measure for prevention improvement, we suggest considering weaning of vaccine-derived immunity, and re-vaccination of girls at fertile age.
Keywords: fulminant SSPE, vaccination, measles, children